Kakuma as a Marketplace : A Consumer and Market Study of a Refugee Camp and Town in Northwest Kenya - International Finance Corporation (International Finance Corporation, Washington, DC, 2020)
In a remote area of northwest Kenya lies a sprawling mass of tents and shelters made of mud brick and cement blocks. It is Kakuma camp, one of the largest and longest-standing refugee camps in the world, which was established in 1992 for refugees fleeing conflict in Sudan. Set on the border of the town of Kakuma, home to Kenya’s Turkana people, Kakuma camp is a melting pot of more than 160,000 refugees and displaced people from South Sudan, Somalia, Ethiopia, Burundi, the Democratic Republic of the Congo, and Sudan. The aim of this study is to better understand Kakuma as a potential market and identify business opportunities and challenges for the private sector. The study identified three types of players that might benefit from its findings namely, commercial firms (banks, microfinance institutions, telecommunications companies, and small and medium enterprises from other sectors), social enterprises (companies that look to attain and maximize financial, social, and environmental impacts) and local entrepreneurs (from the refugee and host communities). By collecting empirical data on revenues, consumption patterns, consumer preferences, and financial transactions in the refugee camp and neighboring town, the study addresses the lack of market information that is necessary for the identified private sector players to start or scale up their operations in the Kakuma area.